113k views
5 votes
Pls help me I don't get it.
Pls indicate steps

Pls help me I don't get it. Pls indicate steps-example-1
User Odile
by
6.1k points

2 Answers

2 votes

I'm having trouble reading, could you type out what is on the picture? I'll edit my answer then.

User Dail
by
5.6k points
3 votes

Answer:

x = -3, y = 3

Explanation:

multiply the equation 3y - x = 12 by 3:

=> 9y - 3x = 36

now add the two equation 9y - 3x = 36 and 3x + 4y = 3 together to eliminate x and solve for y:

=> 9y - 3x = 36

+) 4y + 3x = 3

______________

13y = 39

=> y = 3

substitute y = 3 into the original equation 3y - x = 12 to solve for x:

3(3) - x = 12

=> -x = 12 - 9

=> -x = 3

=> x = -3

User Muaz Usmani
by
5.3k points